2008
DOI: 10.1002/kin.20321
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent kinetics study of the gas‐phase reactions of atomic chlorine with acetone, 2‐butanone, and 3‐pentanone

Abstract: A laser flash photolysis-resonance fluorescence technique has been employed to study the kinetics of the reactions of atomic chlorine with acetone (CH 3 C(O)CH 3 ; k 1 ), 2-butanone (C 2 H 5 C(O)CH 3 ; k 2 ), and 3-pentanone (C 2 H 5 C(O)C 2 H 5 ; k 3 ) as a function of temperature (210-440 K) and pressure (30-300 Torr N 2 ). No significant pressure dependence is observed for any of the reactions studied. Arrhenius expressions (units are 10 −11 cm 3 molecule −1 s −1 ) obtained from the data are k 1 (T) = (1.53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
(83 reference statements)
4
26
0
Order By: Relevance
“…Yield measurements for re-action pathway 1b revealed that the upper limit for the adduct-formation pathway (reaction (1b)) is less than 0.1%, in the temperature range 273-363 K and at the very-low-pressure regime (<3 mTorr). The E a /R value (608 ± 16) K, obtained by absolute rate measurements, is in excellent agreement with the value (594 ± 33) K reported by Zhao et al [17]. Moreover, there is satisfactory agreement with the value (628 ± 25) K obtained by Orlando et al [15], by accepting the latest NASA/JPL Arrhenius expression for the reference reaction of Cl atoms with CH 2 Cl 2 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Yield measurements for re-action pathway 1b revealed that the upper limit for the adduct-formation pathway (reaction (1b)) is less than 0.1%, in the temperature range 273-363 K and at the very-low-pressure regime (<3 mTorr). The E a /R value (608 ± 16) K, obtained by absolute rate measurements, is in excellent agreement with the value (594 ± 33) K reported by Zhao et al [17]. Moreover, there is satisfactory agreement with the value (628 ± 25) K obtained by Orlando et al [15], by accepting the latest NASA/JPL Arrhenius expression for the reference reaction of Cl atoms with CH 2 Cl 2 .…”
Section: Discussionsupporting
confidence: 89%
“…4. Our study resolves the systematic discrepancy between the absolute rate measurements [9,13,17] and the consistently lower (ca. 1.3 times) relative rate determinations [11,12,14,15,26].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations